The risk of developing type 2 diabetes mellitus among the students of Hail University, Saudi Arabia - Abd El-Razik Siam, Bahia Glalal; Abdou Rizk, Shimaa Mohamed; Mahmoud, Soha Kamel Mosbah (Frontiers in Public Health, 2023)
Background: Globally, it is estimated that approximately 537 million adults are living with diabetes. Of them, more than 90% have type 2 diabetes (T2DM). In 2023, a previous meta-analysis showed that the prevalence of T2DM among the general adults' population in Saudi Arabia was 28%. The current study was conducted to assess the risk for developing T2DM among the students of Hail University, Saudi Arabia.This cross-sectional study was conducted in 2022/2023, among census sample of 740 students (both genders, aged 17 to 26 years), who studying at nine colleges of Hail University, Saudi Arabia. The diabetes risk score was assessed using the Australian Type 2 Diabetes Risk Assessment Tool (AUSDRISK). Anthropometric measurements were measured and recorded using standard methods. Socio-demographic variables were also, obtained with an interview-based questionnaire. Statistical analysis was performed usingResults: A total of 740 students were included in the final analysis. Of them 274 (37.0%) were males and 466 (63.0%) were females. The mean age of the study participants is 19.9±1.6 years. The findings showed that 61.9% of the study participants were at intermediate, and high risk of diabetes (59.7% and 2.2%, respectively). The majority 85.7% of males' students were at intermediate risk of diabetes, and 5.8% were at high risk of diabetes. While 44.4% of females' students were at intermediate risk of diabetes, and none of them were at high risk of diabetes. For the following variables (age, gender, college name, area of the university, academic years, weight, height, and BMI) the differences were statistically significant between different categories of diabetes risk scores (P values < 0.005).More than half of the students at Hail University of Saudi Arabia have intermediate, and high risk of T2DM. Males are at a higher risk compared to females. The high risk of T2DM among the university students should be seriously considered.